Behandlung psychischer und psychosomatischer Beschwerden: Inanspruchnahme, Erwartungen und Kenntnisse der Allgemeinbevölkerung in Deutschland = Treatment of mental and psychosomatic complaints : how the general population in Germany gets treatment, and what it expects and knows about treatment alternatives - Larisch, Astrid; Heuft, Gereon; Engbrink, Svenja; Brähler, Elmar; Herzog, Wolfgang; Kruse, Johannes (Zeitschrift für psychosomatische Medizin und Psychotherapie, 2013)
Treatment of mental and psychosomatic complaints - How the general population in Germany gets treatment, and what it expects and knows about treatment alternatives Objectives: The healthcare sector provides a wide range of services with various treatment approaches for mental or psychosomatic complaints. The present study assesses treatment preferences and knowledge within the general population in Germany. Methods: In 2011, a total of n = 2555 individuals aged 14-97 years were interviewed as part of a representative population survey. Using a structured interview, we examined the retrospective, current, and prospective utilization of outpatient psychotherapy, treatment preferences, and knowledge of the alternatives. Results: Outpatient psychotherapy was currently or in the past used by 7.1% of respondents, inpatient psychotherapy by 3.2%. Medical psychotherapists were consulted by 12.5%, psychological psychotherapists by 8.8%of the respondents.Future treatment expectationswere directed more frequently towards medical thanpsychologicalpsychotherapists.Theprimary carephysician continues to play a pivotal role in the treatment of mental/psychosomatic disorders. Treatment expectations were largely independent of the type of disorder.Women were nearly twice as likely as men to utilize or have utilized outpatient psychotherapy (9.1%vs. 4.8%). Discussion: The existing outpatient care for patients with mental or psychosomatic complaints is well accepted among large parts of the the population. For mental or psychosomatic problems, the majority of respondents prefer a medical psychotherapist. Further research needs to clarify which factors determine this preference.
Online veröffentlicht: Apr 2014
Gesehen am 12.10.2021